Prostate Biopsy up Date (Bangladesh Journal of Urology, 2020)
The prostate biopsies are usually performed by urologists in the office setting using trans rectal ultrasound (TRUS) guidance. Current standard of care involves obtaining usually 12 cores from different anatomical sections. These biopsies are usually not directed into a specific lesion as most prostate cancers are not visible on TRUS. Color- Doppler, ultrasound contrast agents, elastography, MRI, and MRI/ultrasound fusion are proposed as imaging methods to guide prostate biopsies. Prostate MRI and fusion biopsy create opportunities for diagnostic and interventional radiologists to play an increasingly important role in the screening, evaluation, diagnosis, targeted biopsy, surveillance and focal therapy of the prostate cancer patient.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.145-157